THE EFFECTIVENESS OF USING EWA APPLICATION TO IMPROVE THE VOCABULARY MASTERY AT SMPN 2 TANJUNGANOM NGANJUK - Reni Oktavia; Sujono SUJONO (Journal of English Language Education, 2026)
After conducting an observation at SMPN 2 Tanjunganom, it was found that many eighth-grade students experienced significant difficulties in mastering English vocabulary. These difficulties include four main indicators: rote memorization, poor retention, misuse in context, and pronunciation. This study employed a quantitative approach with a quasi-experimental design, specifically the post-test only control group design. The post-test instrument consisted of 20 multiple-choice questions representing four vocabulary mastery problem indicators. The data were analyzed using descriptive and inferential statistics through the Independent Sample t-Test with the assistance of SPSS version 25. The results showed that the value of tcount > ttable (8,079 > 1.670) and the Sig. (2-tailed) value was 0.000 < 0.05. Therefore, the null hypothesis (H₀) was rejected and the alternative hypothesis (Hₐ) was accepted. This indicates that there is a significant difference in vocabulary mastery between students taught using the EWA application and those who were not.